The prevalence and determinants of physical activity promotion by Australian chiropractors: A cross sectional study. (August 2019) - Fernandez, Matthew; Moore, Craig; Eklund, Andreas; Swain, Michael; de Luca, Katie; Sibbritt, David; Adams, Jon; Peng, Wenbo
Highlights: Five out of every six Australian chiropractors incorporate physical activity discussions as part of their clinical management. Chiropractors who often discuss physical activity with patients, often discuss occupational health and safety (odds ratio [OR] = 6.10). Chiropractors who often discuss physical activity, often discuss diet/nutrition (OR = 4.56) and smoking/drugs/alcohol (OR = 4.41). Chiropractors who often discuss physical activity are more likely to frequently use exercise therapy/rehabilitation/injury taping (OR = 3.76). Chiropractors who often discuss physical activity are more likely to treat athletes or sports people (OR = 2.18). Abstract: Background: Approximately one in four adults do not meet the World Health Organisation physical activity recommendations. While health promotion (i.e., physical activity) is common within chiropractic settings, little is known about chiropractors discussing this public health issue with their patients. The aim of our study is to examine the prevalence and characteristics of Australian chiropractors who frequently discuss patient physical activity. Methods: A national cross-sectional survey of chiropractors focusing upon practitioner characteristics, practice settings and clinical management characteristics. Regression analyses were conducted on 1924 survey respondents to identify factors associated with practitioners who frequently discuss physical activity with patients. Results: Eighty-five percent of Australian chiropractors reported 'often' discussing physical activity as part of their patient management. The strongest factors associated with chiropractors who frequently discuss physical activity obtained from the multivariate analysis include: often discussing occupational health and safety (odds ratio [OR] = 6.10; 95%CI: 3.88, 9.59), often discussing diet/nutrition (OR = 4.56; 95%CI: 3.12, 6.66), often discussing smoking/drugs/alcohol (OR = 4.41; 95%CI: 2.06, 9.40), often use of specific exercise therapy/rehabilitation/injury taping (OR = 3.76; 95%CI: 2.62, 5.39) and often caring for athletes or sports people (OR = 2.18; 95%CI: 1.56, 3.06) within their practice setting. Conclusion: Discussing physical activity is a frequent feature of patient management among most chiropractors in Australia. The association between these practitioners and discussion of other costly public health burdens could suggest chiropractors have a valuable role to play in chronic disease prevention. Given the growing need for practitioner-led promotion of patient physical activity further research examination of the role and contribution of chiropractors in promoting this important public health topic among patients and communities is needed.